The Stamp act crisis prologue to revolution, - Morgan, Edmund S. (Edmund Sears), 1916-2013; Morgan, Helen M. (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia., 1953)
The Stamp Act, the first direct tax on the American colonies, provoked an immediate and violent response. This book identifies the issues that caused the confrontation and explores the ways in which the conflict was a prelude to the American Revolution.